Transport Infrastructure and Welfare : An Application to Nigeria - Ali, Rubaba (World Bank, Washington, DC, 2015)
Transport infrastructure is deemed to be central to development and consumes a large fraction of the development assistance envelope. Yet there is debate about the economic impact of road projects. This paper proposes an approach to assess the differential development impacts of alternative road construction and prioritize various proposals, using Nigeria as a case study. Recognizing that there is no perfect measure of economic well-being, a variety of outcome metrics are used, including crop revenue, livestock revenue, non-agricultural income, the probability of being multi-dimensionally poor, and local gross domestic product for Nigeria. Although the measure of transport is the most accurate possible, it is still endogenous because of the nonrandom placement of road infrastructure. This endogeneity is addressed using a seemingly novel instrumental variable termed the natural path: the time it would take to walk along the most logical route connecting two points without taking into account other, bias-causing economic benefits. Further, the analysis considers the potential endogeneity from nonrandom placement of households and markets through carefully chosen control variables. It finds that reducing transportation costs in Nigeria will increase crop revenue, non-agricultural income, the wealth index, and local gross domestic product. Livestock sales increase as well, although this finding is less robust. The probability of being multi-dimensionally poor will decrease. The results also cast light on income diversification and structural changes that may arise. These findings are robust to relaxing the exclusion restriction. The paper also demonstrates how to prioritize alternative road programs by comparing the expected development impacts of alternative New Partnership for Africas Development projects.